THE EFFECTS OF CREDIT FINANCING IN AGRICULTURE ON THE DOMESTIC PRODUCT IN AGRICULTURE IN THE REPUBLIC OF SERBIA - Ranisavljević, Duško (Ekonomija - teorija i praksa, 2021)
In recent years, the banking sector has increasingly turned to the agricultural sector. There is a noticeable increase in the total claims of the banking sector from registered farms in the period 2012-2020, while the part of the domestic product generated by the agricultural sector also recorded growth, but not in the same percentage as bank loans to agriculture. The aim of this paper is to examine the interdependence of the increase in total claims of banks on registered agricultural producers with the increase in the domestic product generated by the agricultural sector. The method of statistical correlation was used in this paper. The impact and changes of investment loans in agriculture, loans for working capital, but also the change in bank claims from agricultural producers based on interest and fees have been analyzed. The conclusion is that there is a connection between loans and the domestic product of the agricultural sector, but that there are other factors that have an impact, too. Although in recent years the banking sector has been more open to the agricultural sector and although loans have become more affordable, it is necessary to create conditions for even greater availability of loans to agricultural producers, which would create positive effects on agriculture.